Ocenjevanje kot dejavnik spodbujanja kompetence učenje učenja - Ivanuš-Grmek, Milena (Revija za elementarno izobraževanje, 2014)
The paper presents the learning to learn competence, and teacher's role in promoting its development through assessment and providing feedback. Teaching for learning to learn affects teacher behavior in the classroom, resulting in greater accountability and in revised attitudes towards the students. From teachers it requires a different conception of their own knowledge, teaching and learning, and contributes to increased autonomy of learners. Among the factors of learning school can influence assessment and self-assessment and the content and forms of feedback were exposed. The survey results remind us that a majority of participating teachers in basic school estimate they perform the activities to promote learning to learn carried relatively frequently, there are, however, differences depending on teachers' work experience.
Keywords: learning to learn; učenje učenja; ocenjevanje; knowledge assessment; samoocenjevanje; self-assessment; preverjanje znanja; feedback; povratne informacije; osnovne šole